Age and premorbid intelligence suppress complaint-performance congruency in raw score measures of memory - Merema, M.; Speelman, C.; Kaczmarek, E.; Foster, Jonathan (Cambridge University Press, 2012)
Background: We aimed to examine the role of age and premorbid intelligence (IQ) in suppressing the relationship between subjective memory complaints (SMCs) and raw score memory performance. Methods: We used a community sample of older adults aged 66–90 years (N = 121) to test whether the inclusion of age and a premorbid IQ measure in multiple regression analyses increased semipartial correlations of raw score memory performance in predicting SMCs. Rank contrast correlations were also carried out to observe how age and premorbid IQ are related to complaint–performance congruency. Measures utilized in the study included the Memory Functioning Questionnaire (for SMCs), Visual Reproduction and Logical Memory Subtests (memory performance), and the National Adult Reading Test (premorbid IQ). Results: Inclusion of age and premorbid IQ in the multiple regression analyses increased semipartial correlations for all raw score measures of memory. Both age and premorbid IQ were significantly related to complaint–performance congruency, whereby older participants and those with lower premorbid IQ scores rated their memory abilities more leniently than younger and higher premorbid IQ participants. Conclusion: The results suggest differences in age and premorbid IQ play a small role in suppressing the relationship between SMCs and memory performance when utilizing raw score measures of memory.